2014
DOI: 10.1017/s1431927614001688
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Quantification for 3D Energy Dispersive Spectrometry: Going Beyond the Limitation of Large Volume of X-Ray Emission

Abstract: This paper presents a method developed to quantify three-dimensional energy dispersive spectrometry (3D EDS) data with voxel size smaller than the volume from which X-rays are emitted. The influence of the neighboring voxels is corrected by applying recursively a complex quantification, improving thereby the accuracy of the quantification of critically small features. The enhanced quantification method is applied to simulated and measured data. A systematic improvement is obtained compared with classical quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The system is ambiguous and convergence to a local minimum is likely. In [14] , the most unfavourable cases are avoided by grouping layers of similar composition together. The situation is improved, but inaccurate solutions still lead to an artefact of over-correction, as observed with simulated data ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The system is ambiguous and convergence to a local minimum is likely. In [14] , the most unfavourable cases are avoided by grouping layers of similar composition together. The situation is improved, but inaccurate solutions still lead to an artefact of over-correction, as observed with simulated data ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Described in [14] , the enhanced quantification for 3D EDS–SEM is revisited and augmented here. The standard quantification, called here bulk quantification, is first considered.…”
Section: Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, by FIB thinning the samples and analyzing them at high voltages using a FEG-EPMA, Kubo et al (2013) demonstrated a spatial resolution in the range 40–200 nm for an InGaP/GaAs thin sample, with detection limits of 1,000–10,000 ppm and signal-to-noise ratio 13 times higher than that of a STEM-EDS system (on bulk samples such detection limits would be 2 to 3 orders of magnitude lower). Worth mentioning is also the development of three-dimensional microanalysis in dual-beam instruments (i.e., SEM equipped with both EDS and FIB), which will require more sophisticated quantification methods such as the one recently developed by Burdet et al (2014).…”
Section: A Look Into the Futurementioning
confidence: 99%